Medication adherence among hospitalized hypertension patients in Shenyang city - Wenqi NING; Ding LI; Liping YANG; Yuxian ZHANG; Hongzhu LIU; Rui HU; Mingzhu CHEN; Tong MENG; Min JIA; Ran ZHANG; Chang LU; Jian GONG (Zhongguo gonggong weisheng)
ObjectiveTo provide a reference for improving medication adherence among hypertensive patients in Shenyang. MethodsOne thousand hypertensive patients hospitalized between January 1, 2020, and January 1, 2021, in Shenyang city were randomly selected. An adherence evaluation scale was used to assess patient adherence to antihypertensive medications. Patients were grouped according to their adherence level (good adherence as the observation group and poor adherence as the control group). Descriptive analysis was used to compare baseline characteristics, including sociodemographic characteristics, and to compare adherence between groups. Statistical analysis was performed using SPSS 22.0 statistical software. ResultsAmong the 1 000 hospitalized hypertensive patients in Shenyang city, 35.20% showed good medication adherence, while 64.80% showed poor adherence. The proportion of patients with good medication adherence gradually decreased with increasing hypertension grade. Access to pharmaceutical services, perceived social support, awareness of hypertension, and utilization of social support were beneficial in improving patient adherence. ConclusionsFocusing on factors such as awareness of hypertension, accessible perceived social support, utilization of social support, provision of pharmaceutical services, and strengthening publicity and education, to enhance patient initiative, can improve medication adherence among hospitalized hypertensive patients.